Effect of Three Different Remineralizing Agents on White Spot Lesions; AnIn Vitro Comparative Study - Soodeh Tahmasbi; Mahya Adhami; Azam Valian; Roya Hamedi (Islamic Dental Association of Iran, 2016)
Background and Aim: White spot lesions (WSLs) are common occurrence following orthodontic treatment, this study sought to compare the remineralizing potential of fluoride, MI Paste Plus (CPP-ACP-F) and Remin Pro for treatment of WSLs. Materials and Methods: This in vitro study was conducted on 56 sound human premolars that extracted for orthodontic purposes. Teeth were cleaned and their roots were cut, then the crowns were mounted in acrylic resin. Teeth surfaces were coated with nail varnish except for a 3×4mm window on the buccal surface. In order to create WSLs, all samples were immersed in demineralizing solution for 10 days. After surface hardness was measured using a Vickers microhardness tester, teeth were randomly divided into four groups. In control group (group 1) no remineralizing agent was used while, groups 2 to 4, were treated with0.05% sodium fluoride (NaF), MI Paste Plus, and Remin Pro paste respectively, for five minutes every 12hours. After each treatment, specimens were immersed in freshly prepared artificial saliva. At the end of 28 days, surface microhardness was measured again and changes were statistically analyzed using analysis of covariance (ANCOVA). Results: The mean changes in surface microhardness of MI Paste Plus, NaF and Remin Pro groups was significantly higher than control group (P˂0.001, P˂0.001 and P0.046 respectively). Conclusion: MI Paste Plus, 0.05% NaF mouthwash, and to a lesser extent Remin Pro were efficient for treatment of WSLs comparing to the artificial saliva.